Endoscopic management of retrocalcaneal pain: a prospective observational study - Meena, Mukesh Kumar; Kalra, Mukesh; Singh, Suryakant; Meena, Sanjay; Jangira, Vivek; Chouhan, Dushyant; Chaudhary, Neha (International Journal of Research in Orthopaedics, 2020)
Background: In an effort to reduce morbidity and complications of open surgery, an endoscopic technique was used for the management of the conditions leading to retrocalcaneal pain. With this purpose, the current study was undertaken to evaluate results of endoscopic management of retrocalcaneal pain using American orthopaedic foot and ankle score (AOFAS). Methods: 20 patients (26 heels) in the age group 18-80 years presenting with retrocalcaneal pain not responding to conservative management underwent endoscopic decompression of the retrocalcaneal bursae and excision of bony spurs. Two portals were created, one laterally and one medially, over the posterosuperior portion of the calcaneus to gain access to the retrocalcaneal space. The inflamed bursal tissue was identified and removed, and the prominent bone was resected. The functional outcome was evaluated pre and postoperatively with the AOFAS. Results: 70% patients have retrocalcaneal bursitis, 20% Haglund’s deformity as confirmed on lateral view of ankle X-ray and only 10% of non-insertional tendinosis. Mean operative time was 54.95 minutes. Mean duration of hospital stay was 3.90±0.64 and the mean follow-up was 66 days (range 30-180 days). The average AOFAS score improved from 65.60 points pre-operatively to 96.80 points at final follow-up. There were fifteen excellent results, seven good results, two fair results and two poor results. Conclusions: Endoscopic procedure for retrocalcaneal bursitis and Haglund deformity seemed to be a safe and efficacious option for surgical treatment of retrocalcaneal pain.